Analisis Syi’ir Lagu Wasiat Kanjeng Sunan Drajat (Kajian Semantik) - Nurfadillah, Ike; Kustiana, Lidia; Sulistyowati, Heny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Artikel ini menganalisis syi’ir lagu